Physiology and transcriptomics of water-deficit stress responses in wheat cultivars TAM 111 and TAM 112 - Reddy, Srirama Krishna; Liu, Shuyu; Rudd, Jackie C.; Xue, Qingwu; Payton, Paxton; Finlayson, Scott A.; Mahan, James; Akhunova, Alina R.; Holalu, Srinidhi V.; Lu, Nanyan (My University, 2014)
Hard red winter wheat crops on the U.S. Southern Great Plains often experience moderate to severe drought stress, especially during the grain filling stage, resulting in significant yield losses. Cultivars TAM 111 and TAM 112 are widely cultivated in the region, share parentage and showed superior but distinct adaption mechanisms under water-deficit (WD) conditions. Nevertheless, the physiological and molecular basis of their adaptation remains unknown. A greenhouse study was conducted to understand the differences in the physiological and transcriptomic responses of TAM 111 and TAM 112 to WD stress. Whole-plant data indicated that TAM 112 used more water, produced more biomass and grain yield under WD compared to TAM 111. Leaf-level data at the grain filling stage indicated that TAM 112 had elevated abscisic acid (ABA) content and reduced stomatal conductance and photosynthesis as compared to TAM 111. Sustained WD during the grain filling stage also resulted in greater flag leaf transcriptome changes in TAM 112 than TAM 111. Transcripts associated with photosynthesis, carbohydrate metabolism, phytohormone metabolism, and other dehydration responses were uniquely regulated between cultivars. These results suggested a differential role for ABA in regulating physiological and transcriptomic changes associated with WD stress and potential involvement in the superior adaptation and yield of TAM 112.
Citation: Reddy, S. K., Liu, S., Rudd, J. C., Xue, Q., Payton, P., Finlayson, S. A., … Lu, N. (2014). Physiology and transcriptomics of water-deficit stress responses in wheat cultivars TAM 111 and TAM 112. Retrieved from http://krex.ksu.edu
Keywords: Abscisic acid; TAM 111; TAM 112; Transcriptomics; Water-deficit stress; Wheat